ANALISIS BESARNYA PAJAK BPHTB DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN KEDIRI (Studi Kasus Pada Bapenda Kabupaten Kediri) - Aidha Novita Sari; Fauziyah Fauziyah; Putri Awalina (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
This study aims to determine the amount of BPHTB tax and its contribution to local revenue at Bapenda Kediri Regency. This study uses a quantitative descriptive method by analyzing the data obtained through interviews and documentation. Based on the data analysis conducted, the results show that the largest percentage of BPHTB tax realization was in 2018 of 348.73%, while the largest percentage of realization of regional original income in 2018 was 134.86%, and the largest percentage of contribution in 2018 was 25.48%. From these results it is concluded that 2018 is the largest contributor to regional income from the year before and after, due to the large number of land sales or purchases transactions. It is recommended that the Kediri Regency Bapenda carry out BPHTB tax management, this is because BPHTB taxes have great potential in increasing local revenue. Keywords: BPHTB Tax, Contribution, Local Revenue.